Decoupled optimal power flow simulation to maximize customer welfare - Ong, Yao Zhou (2018)
The purpose of this project is to study the feasibility of utilizing the DC-Optimal Power Flow (OPF) solution to maximize customer’s welfare in a real-world AC setting. DC-OPF is an approximation of the conventional OPF, where a standard DC-OPF formulation neglects losses and reactive power in the system and assumes that all the buses in the system have a flat voltage magnitude of 1 per unit (pu). In addition, Demand Side Management (DSM) will be incorporated into the DC-OPF formulation to simulate customer’s participation, which will further reduce the cost of generation and maximize the welfare of customers. Due to the simplifications made, DC-OPF solutions do not guarantee AC feasibility. An iterative validation process proposed will be used to test for the AC feasibility of a DC-OPF solution on a realistic AC simulation environment. Rectifications will be made if system violations are found, and the process will repeat until an AC feasible DC-OPF solution is obtained. The IEEE 14-bus system and 15-bus microgrid from NTU’s Clean Energy Research Laboratory (CERL) will be used for the study in this project. Results show that with the validation process proposed, DC-OPF solutions can be used in a real-world AC setting. Despite a difference in the solution of an AC feasible DC-OPF and DC-OPF, the difference is within acceptable limits. Furthermore, the use of DSM can tremendously improve the overall time taken to obtain an AC feasible DC-OPF solution and further maximize the welfare of customers.